Черный обелиск: романы / пер. с нем. В. Станевич - Ремарк Эрих Мария (Книга и бизнес : Кром, 1993)
Экземпляры: (20200207) / Инвентарный номер: 29418 / Цена: 25.00 / Сис.шифр: 84(4/8) / Авт.знак: Р 37 / ББК: 84(4Гем)